Construction Of International Student Satisfaction Model Under The Internationalization Of Higher Education：New Normal Perspective (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Under the development trend of the globalization of higher education, international students’ satisfaction has become an important research issue of academic circles. The purpose of this study is to develop a conceptual framework to understand the key antecedent and consequent constructs of international student satisfaction in Chinese universities. We reviewed the related research published since 1986 and analyzed 7 antecedent dimensions (student expectations, service quality, image, perceived value, educational outcomes, campus facilities, academic experience) and 1 consequent dimensions (student loyalty). Based on the expectation-disconfirmation Theory and Customer Satisfaction Theory, we identified the key factors related to satisfaction and formed a conceptual model of student satisfaction. For further research, we will use stratified sampling to select 500 international students to conduct a questionnaire survey from 5 universities in Guangxi, China. The conceptual model and possible outcome will help us better understand the main predictors of international student satisfaction and the impact of international students’ satisfaction on future behavior intentions, which will provide implications for scholars and policymakers in this field.